The psychology of family law - Brank, Eve M. (New York : New York University Press, 2019)
Although family law is diverse and does not fit into a neat theoretical statement as do many other areas of law, one consistent theme is present in family law-human behavior. Although relying too heavily and uncritically on empirical data and conclusions can be risky, there is promise and utility in empirical science applied to family law. This text focuses on the premise that empirical research in family law can lead to better outcomes in many situations.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 12, 2019).
Keywords: Domestic relations; Domestic relations -- Psychological aspects; Law; Laws of specific jurisdictions & specific areas of law